Cancer-associated adipocytes: emerging supporters in breast cancer - Zhao, Chongru; Wu, Min; Zeng, Ning; Xiong, Mingchen; Hu, Weijie; Lv, Wenchang; Yi, Yi; Zhang, Qi; Wu, Yiping (Journal of experimental & clinical cancer research, 2020)
Breast cancer (BC) is a malignant breast tumor confronted with high invasion, metastasis and recurrence rate, and adipocytes are the largest components in breast tissue. The aberrant adipocytes, especially the BC-neighbored cancer-associated adipocytes (CAAs), are found in the invasive front of BC. CAAs present a vicious phenotype compared with mature mammary adipocytes and mediate the crosstalk network between adipocytes and BC cells. By releasing multiple adipokines such as leptin, adiponectin, interleukin (IL)-6, chemokine ligand 2 (CCL2) and chemokine ligand 5 (CCL5), CAAs play essential roles in favor of proliferation, angiogenesis, dissemination, invasion and metastasis of BC. This article reviews the recent existing CAAs studies on the functions and mechanisms of adipocytes in the development of BC, including adipokine regulating, metabolic reprogramming, extracellular matrix (ECM) remodeling, microRNAs (miRNAs) and immune cell adjusting. Besides, adipocyte secretome and cellular interactions are implicated in the intervention to BC therapy and autologous fat grafting of breast reconstruction. Therefore, the potential functions and mechanisms of CAAs are very important for unveiling BC oncogenesis and progress. Deciphering the complex network between CAAs and BC is critical for designing therapeutic strategies and achieving the maximum therapeutic effects of BC.